2018
DOI: 10.48550/arxiv.1808.05331
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the Convergence of Learning-based Iterative Methods for Nonconvex Inverse Problems

Abstract: Numerous tasks at the core of statistics, learning and vision areas are specific cases of ill-posed inverse problems. Recently, learning-based (e.g., deep) iterative methods have been empirically shown to be useful for these problems. Nevertheless, integrating learnable structures into iterations is still a laborious process, which can only be guided by intuitions or empirical insights. Moreover, there is a lack of rigorous analysis about the convergence behaviors of these reimplemented iterations, and thus th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…More recently, more and more examples showed that the unrolling dynamics approach seems a good balance between model interpretability and efficacy. This includes unrolling discrete forms of nonlinear diffusions for image restoration [98,38] and unrolling optimization algorithms for medical imaging and inverse problems [139,2,136,37,97,87,168]. The unrolling dynamics approach can often result in deep models that have better interpretability inherited from the original dynamics.…”
Section: When Handcraft Modeling Meets Deep Learningmentioning
confidence: 99%
“…More recently, more and more examples showed that the unrolling dynamics approach seems a good balance between model interpretability and efficacy. This includes unrolling discrete forms of nonlinear diffusions for image restoration [98,38] and unrolling optimization algorithms for medical imaging and inverse problems [139,2,136,37,97,87,168]. The unrolling dynamics approach can often result in deep models that have better interpretability inherited from the original dynamics.…”
Section: When Handcraft Modeling Meets Deep Learningmentioning
confidence: 99%